POLICY DEVELOPMENT FOR THE ENERGY MIX IN INDONESIA USING SYSTEM DYNAMICS - Sani, Kartono
National Energy Vision is designed to manage a sustainable balance of energy supply and demand through sorting out the energy challenges in acquiring quality resources at an affordable cost and with due respect the environment. In Indonesia, through the Presidential Regulations No.5/2006 and No.79/2014 on the national energy policy, the government introduced the National Energy Mix 2025 and 2050 successively, aimed at improving the portfolio by means of suppressing the burning of fossil fuels while gradually increase the uses of renewable resources. Most recently, through the Presidential Regulation No. 22/2017 on General Planning of National Energy or well known as RUEN, the government details the energy vision with all the projections of demand and supply until 2050. In reality, Statistics show continuously declining oil lifting, ramping up imported oil, uncontrollable exploitation of environmentally unfriendly coal, and stagnant growth of new and renewable energy (NRE) technologies. The country is facing tremendous challenges prior to developing a steady energy vision. With those premises, this research is to introduce new approaches of preference in examining the national Energy Mix Vision, discusses qualitative models of the current energy circle against the proposed one, share the results of simulation and the quantitative modelling challenges. It is designed to prove that the modeling - examined by statistical analyses on the past performance - may simply simulate the dynamically complex realm prior to being rerun and compared to the linear, non-simulation model of General Planning of National Energy (RUEN) to examine appropriateness of the new model to be able to offering more reliable alternative the development of energy policies towards the vision. The literature review defines System Dynamics as the preferred modelling approach. The qualitative model finds the presence of “energy vicious circle” in the country energy management, while empirical data of the supply mix trends demonstrate the past problematic behaviors in implementing the energy vision. The initial quantitative model fairly succeed in simulating the historical trends and validates the model structure. Resetting, upgrading and reruns of the simulation model towards the future suggest a more realistic energy mix pattern compared to the existing and so may be offering a more reliable solution. It reveals that the RUEN projections for fossil energies are mostly too optimistic, while the other way around for renewables.